Preconditioning strategy in rugby-7s players: Beneficial or detrimental? - Marrier, B.; Durguerian, A.; Robineau, J.; Chennaoui, M.; Sauvet, F.; Servonnet, A.; Piscione, J.; Mathieu, B.; Peeters, A.; Lacome, M.; Morin, J.-B.; Le Meur, Y. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Preconditioning strategies are considered opportunities to optimize performance on competition day. Although investigations conducted in rugby players on the effects of a morning preconditioning session have been done, additional work is warranted. The aim of this study was to monitor changes in physical and psychophysiological indicators among international Rugby-7s players after a priming exercise. Methods: In a randomized crossover design, 14 under-18 international Rugby-7s players completed, at 8:00 AM, a preconditioning session consisting of a warm-up followed by small-sided games, accelerations, and 2?×?50-m maximal sprints (Experimental), or no preloading session (Control). After a 2-h break, the players performed a set of six 30-m sprints and a Rugby-7s match. Recovery-stress state and salivary stress-marker levels were assessed before the preloading session (Pre), immediately after the preloading session (Post 1), before the testing session (Post 2), and after the testing session (Post 3). Results: Experimental-Control differences in performance across a repeated-sprint test consisting of six 30-m sprints were very likely trivial (+0.2, ±0.7%, 3/97/1%). During the match, the total distance covered and the frequency of decelerations were possibly lower (small) in Experimental compared with Control. Differences observed in the other parameters were unclear or possibly trivial. At Post 2, the perceived recovery-stress state was improved (small difference) in Experimental compared with Control. No difference in salivary cortisol response was observed, while the preconditioning session induced a higher stimulation of salivary testosterone and a-amylase. Conclusions: The players` ability to repeat sprints and physical activity in match play did not improve, but their psychophysiological state was positively affected after the present preconditioning session.